Scrotal wall metastasis from a primary lung adenocarcinoma - Marie-Louise M. Coussa-Koniski; Pia A. Maalouf; Nehme E. Raad; Noha A. Bejjani (Respiratory Medicine Case Reports, 2015)
This a case of a 77 years old male heavy smoker, known to have Combined Pulmonary Fibrosis and Emphysema complicated by a primary invasive adenocarcinoma of the lung with bone metastasis, who presented with a two weeks history of right inguino-scrotal pain and swelling. Imaging studies revealed a right paratesticular formation that appeared to involve the epididymis and the scrotal wall. A biopsy of the mass showed morphological and Immunophenotypic features in favor of metastasis of an adenocarcinoma of the lung. Based on our literature review, there are only few published cases about scrotal wall metastasis of a lung primary.